Vinylogous Annulation Cascade Toward Stereoselective Synthesis of Highly Functionalized Indanone Derivatives. Issue 23 (14th October 2019) - Bhajammanavar, Vinod; Mallik, Sumitava; Baidya, Mahiuddin
Abstract: A base promoted vinylogous annulation cascade of alkylidene malononitriles with cyclopentene‐1, 3‐diones with a subsequent reduction sequence has been devised to furnish densely functionalized 3‐hydroxyindanone scaffolds in high yields with excellent diastereoselectivity. Unlike preceding approaches that account for the formation of the pentanoid ring, this strategy features construction of the aromatic ring. The protocol is scalable, displays very broad substrates scope including late‐stage functionalization of bioactive estrone, applicable to activated coumarin system, and is suitable to access an indenoquinoline derivative. Abstract :